2015
DOI: 10.5812/ircmj.17(6)2015.13138
|View full text |Cite
|
Sign up to set email alerts
|

Determining Functional Vitamin B12 Deficiency in the Elderly

Abstract: Background:Elevated concentration of serum total homocysteine usually occurs in vitamin B-12 deficiency. This metabolite can be measured and used for screening functional vitamin B-12 deficiency.Objectives:We assessed functional vitamin B12 deficiency in Tehranian elderly admitted to elderly research center, University of Social Welfare and Rehabilitation Sciences.Patients and Materials:A cross-sectional study was performed on 232 elderly admitted to elderly research center in Tehran, Iran in 2012. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Khodabandehloo et al [16] reported that the mean blood level of vitamin B12 in all subjects was 448.92±156.75 ng/mL. In their diabetic group, the prevalence of B12 deficiency was seen to be above 6%.…”
Section: Discussionmentioning
confidence: 89%
“…Khodabandehloo et al [16] reported that the mean blood level of vitamin B12 in all subjects was 448.92±156.75 ng/mL. In their diabetic group, the prevalence of B12 deficiency was seen to be above 6%.…”
Section: Discussionmentioning
confidence: 89%
“…Elevated circulating total homocysteine (tHcy) concentration is a risk factor for cardiovascular disease. In addition, HHcy in the elderly is strongly associated with depression, impaired cognitive function and dementia 14 . Plasma homocysteine and MMA were usually high due to a low vitamin B12 and folate.…”
Section: Discussionmentioning
confidence: 99%
“…Using a serum B 12 cutoff of 220 pmol/L, an Iranian study found that 56% and 93% of people aged 65-74 and ! 75 years, respectively, were at high risk of B 12 deficiency [177].…”
Section: Malabsorptionmentioning
confidence: 98%